2006
DOI: 10.1021/ol052685j
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature n-Butyllithium-Induced Rearrangement of Allyl 1,1-Dichlorovinyl Ethers

Abstract: [reaction: see text]. Upon treatment with n-BuLi at low temperatures, a variety of allyl 1,1-dichlorovinyl ethers 2 undergo rearrangement to furnish gamma,delta-unsaturated esters 3 after alcohol addition. Compounds containing quaternary centers (3e: R1 = H, R2, R3 = -(CH2)5-; 3f: R1 = H, R2 = CH3, R3 = (CH2)2CH(CH3)2) may be formed in high yield and under mild conditions utilizing this protocol. The reaction is stereospecific and may be applied to the preparation of Delta(2,3)-beta-C-glycosides and alpha,beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…[21] We reasoned that replacement of metallic lithium by organolithium reagents RLi might allow non-terminal alkynes to be prepared in a similar fashion. [22] In fact, treatment of compound 4 as the model substrate with MeLi in Et 2 O resulted in a very clean formation of the corresponding methyl-capped acetylene derivative 5 a (R = Me), but the reaction was slow and excess MeLi had to be used to ensure full conversion (Table 1, entries 1 and 2). The use of THF engendered a much faster rate but led to a slight drop in yield (entry 3).…”
Section: Formation Of Non-terminal Alkynes By Reductive Alkylationmentioning
confidence: 99%
“…[21] We reasoned that replacement of metallic lithium by organolithium reagents RLi might allow non-terminal alkynes to be prepared in a similar fashion. [22] In fact, treatment of compound 4 as the model substrate with MeLi in Et 2 O resulted in a very clean formation of the corresponding methyl-capped acetylene derivative 5 a (R = Me), but the reaction was slow and excess MeLi had to be used to ensure full conversion (Table 1, entries 1 and 2). The use of THF engendered a much faster rate but led to a slight drop in yield (entry 3).…”
Section: Formation Of Non-terminal Alkynes By Reductive Alkylationmentioning
confidence: 99%
“…1–3 Due to their linear geometry, alkynyl ethers are relatively unhindered to approach by functional groups present in the same or different molecules; furthermore, alkynyl ethers can prospectively form up to three new bonds in a single reaction. 4 …”
mentioning
confidence: 99%
“…The previous studies of Katzenellenbogen,15 as well as our own investigations,4 have indicated that allyl-1-alkynyl ethers undergo rapid sigmatropic rearrangement at low temperatures (−33 °C, −78 °C) once formed. Therefore, we wished to assess if sigmatropic rearrangement would also take place upon t -BuOK treatment of α-allyloxy ketone-derived vinyl trifates at −78 °C.…”
mentioning
confidence: 68%
“…We have previously shown that treatment of allyl-1,1-dichlorovinyl ethers with 2.2 equiv of n -butyllithium at −78 °C, followed by quenching of the reaction mixture with excess alcohol, leads to rearranged γ,δ-unsaturated esters in high yield 4. The reaction possesses many of the characteristics of a sigmatropic process, both in terms of its stereospecificity and geometrical requirements.…”
mentioning
confidence: 99%